PROFITABILITY ANALYSIS OF URBAN MASS TRANSPORT LINES USING ACTIVITY-BASED COSTING METHOD: AN EVIDENCE FROM THE CZECH REPUBLIC - Popesko, Boris; Zámečník, Roman; Kolkova, Andrea (Journal of Applied Engineering Science, 2016)
The objective of this study is to present how could be Activity-Based Costing method used for the purpose of the profitability analysis of individual bus and trolleybus lines in an urban mass transport company which operates the land public transport inside the medium sized town in Czech Republic. Activity-Based Costing method had been used, in order to causal allocation of overhead costs to individual operations in order to measure the profitability of particular transport lines. The performed study showed the application process of the Activity-Based Costing and possible information outputs for an urban mass transport company as well as the limitations of the method use in the field of transportation services. The study also analyses the obstacles in effective data collection and processing which implementation team faced during the analysis. The primary limitation of the analysis, is similarly as in other studies, is the quality of the non-financial information which had to be obtained. Study discusses problems related with the fare system, which does not provide the information regarding the route taken by individual passenger. The study presents the how could be ABC method used for the decision making support in urban mass transport company and shows a real example of the ABC system information outputs.